2013
DOI: 10.4021/jocmr1532w
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Heart Failure: A Concise Review

Abstract: The concept of “diastolic” heart failure grew out of the observation that many patients who have the symptoms and signs of heart failure had an apparently normal left ventricular (LV) ejection fraction. Thus it was assumed that since systolic function was “preserved” the problem must lie in diastole, although it is not clear by whom or when this assumption was made. Nevertheless, many guidelines followed on how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…Impaired LV relaxation is associated with hypertension as a major consequence and leads to diastolic dysfunction by adversely affecting the adequate filling of LV. In half of the cases of heart failure, diastolic dysfunctional abnormalities are present with an increased risk of mortality (Aziz, Tk, Enweluzo, Dutta, & Zaeem, 2013). SHR treated with vehicle showed & Contaldo, 1997), (Mattioli, Zennaro, Bonatti, Bonetti, & Mattioli, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Impaired LV relaxation is associated with hypertension as a major consequence and leads to diastolic dysfunction by adversely affecting the adequate filling of LV. In half of the cases of heart failure, diastolic dysfunctional abnormalities are present with an increased risk of mortality (Aziz, Tk, Enweluzo, Dutta, & Zaeem, 2013). SHR treated with vehicle showed & Contaldo, 1997), (Mattioli, Zennaro, Bonatti, Bonetti, & Mattioli, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A slight acute increase in LVEDP after addition of 5‐HMF is difficult to reconcile with an inhibitory action on Ca 2+ channels, but has been observed by others using established Ca 2+ channel blockers in vitro (Amende et al, ; Schmidlin et al, ; Hara et al, ) and in vivo (Kass et al, ; Nishimura et al, ; Cockrill et al, ). It should be noted that these acute effects have to be distinguished from the often observed protective effects after long‐term treatment with Ca 2+ channel blockers on diastolic dysfunction, attributed to indirect haemodynamic improvements (Aziz et al, ). Moreover, it has been suggested that Ca 2+ channel blockers applied at relatively high concentrations interfere with the Ca 2+ uptake and release activity of the sarcoplasmic reticulum in cardiac and skeletal myocytes (Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Diastolic heart failure, or heart failure with preserved ejection fraction (HFpEF) has become increasingly studied and is responsible for half of all heart failure hospitalizations (7, 152, 210, 216). Risk factors for HFpEF include aging, diabetes, obesity, and hypertension, and HFpEF has a higher prevalence in women than men.…”
Section: Biomechanics In LV Hypertrophy and Diastolic Heart Failurementioning
confidence: 99%
“…Similarly, peripheral artery stiffening increases the resistance of the circulatory system leading to hypertension and increased LV pressure (215). HFpEF hearts commonly show concentric remodeling characterized by normal LV volume, increased LV mass (thus decreased volume to mass ratio), increased wall thickness, and increased chamber and myocardial stiffness (7). HFpEF hearts undergo hypertrophy with a marked increase in fibrosis, which leads to increased wall stiffness.…”
Section: Biomechanics In LV Hypertrophy and Diastolic Heart Failurementioning
confidence: 99%